Memahami Pengelolaan Pengungkapan Informasi Pribadi di Media Sosial di Kalangan Dewasa Dini - Arina Sekar Ayu Pertiwi; S. Rouli Manalu (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2018)
This study aims to understand the management of privacy in young adult social media users (18-29), the reasons behind it and how privacy management is carried out on social media. This research is motivated by the emergence of the phenomenon of young adults social media users who have a lot of personal information about them that can be accessed online. While in fact there are many privacy threats that can be experienced by users, such as online harassment, identity theft, and sexual harassment. This study used a sequential mixed method where researcher executed the stage of quantitative research and the qualitative research stage separately. The main theory used in this study is Communication Privacy Management Theory. Data collection techniques were performed by distributing online quantitative questionnaires, and in-depth interviews. This research was conducted on 250 young adult social media users to obtain quantitative data and five young adult social media users to obtain qualitative data. This study found that social media users’ privacy management were shaped by: (1) the views of social media users towards personal information, (2) the perceived benefits of sharing information in social media for users, (3) the technical understanding of the features of privacy settings, (4) the views of users if other users could be trusted or not, and (5) the perception about the possibility of privacy violations and optimistic bias. The majority of individuals revealed that they had their own preferences about personal information that they would not share, so it could be said that the management of private disclosure was a way of regulating privacy, even though this arrangement had its own level depending on the level of privacy desired by the individual. Social media users also use the 'hide story from' feature, 'blocked accounts', 'only certain users', and 'private' profiles for audience segmentation as a manifestation of privacy management on social media.